Answer:
7/20
Step-by-step explanation:
Hope this helped!
Answer:
-x +6
Step-by-step explanation:
We assume you want to simplify this.
Use the distributive property to eliminate the parentheses. That property tells you that the factor outside parentheses (2) will multiply both of the terms inside parentheses. It's as though you had a bag (parentheses) with two objects inside. Two such bags will have two of each of those objects.
2(-x +3) +x
= 2(-x) +2(3) +x
= -2x +6 +x
Now, the like terms -2x and +x can be combined.
= x(-2 +1) +6
= x(-1) +6
= -x +6 . . . . . the simplified expression
Answer:
The volume of the Prism is equal to the volume of the cylinder
Step-by-step explanation:
Because both are 5 units making them equal
React to my new music video Dasgasdom3 East Coast junkie
Step-by-step explanation:
-13 - 23 = -13 + (-23)
= -36
-13 - (-23) = -13 + 23
= 10